States of Delinquency : Race and Science in the Making of California's Juvenile Justice System - Chávez-García, Miroslava, 1968- (Book collections on Project MUSE., 2012)
This unique analysis of the rise of the juvenile justice system from the nineteenth to twentieth centuries uses one of the harshest states--California--as a case study for examining racism in the treatment of incarcerated young people of color. Using rich new untapped archives, States of Delinquency is the first book to explore the experiences of young Mexican Americans, African Americans, and ethnic Euro-Americans in California correctional facilities including Whittier State School for Boys and the Preston School of Industry. Miroslava Chávez-García examines the ideologies and practices used b.